ANALISIS BEBAN KERJA DAN KEBUTUHAN TENAGA KERJA PADA PT ARK XPRESS INTERNASIONAL DI BANTEN - Radna Ningsih; Ratri Kusuma Ningtia (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
PT ARK Xpress Internasional is an express company based on freight forwarding services. In this company the number of workers is not calculated optimally according to workload and labor requirements. This can be seen by the large number of workers unemployed in the warehouse section. The number of unemployed workers is quite large, namely 5 to 6 people from 26 warehouse workers resulting in a large number of unused human resources, so that the company's operational costs are wasted. The purpose of this study is to analyze the workload of each warehouse process employee and the labor requirements. From these problems the authors conducted research on how much the workforce should be needed by the company according to the conditions and situation of the company, by using a work sampling method or random sample by calculating the workload of employees. The results of the study show that workload and labor requirements of 3 out of 5 parts of the warehouse have less workload and excessive labor. So it is recommended to reduce the workforce for power weight measurement and revenue protection 3 people, Vas Team 2 people, and manifest bagging 2 people.